Pengembangan E-Modul Fisika Berbasis PBL Untuk Meningkatkan Keterampilan Kolaborasi Peserta Didik - Damayanti, Indira Surya; Budiawanti, Sri (Universitas Jember, 2024)
The study aims to: 1) develop of PBL-based e-module to improve students collaboration skills, 2) the feasibility of PBL-based e-module to enhance students collaboration skills, and 3) the effectiveness of the PBL-based e-module to enhance students collaboration skills. The research method used Research and Development (R&D) with ADDIE model by Dick and Carry (1996). Research procedures were carried out in four initial stages: analysis, design, development and implementation. The conclusions are: 1) an e-module based PBL characteristics has been successfully developed, 2) based on validation results, e-module meets the criteria to be utilized in learning activities, and 3) this e-module received N-Gain score 0,6053, indicating it is effective for enhancing students collaboration skills. Key words: e-module, PBL, collaboration skills